2019
DOI: 10.3390/ijms20246192
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc in Gliotoxin Biosynthesis of Aspergillus fumigatus

Abstract: Zinc performs diverse physiological functions, and virtually all living organisms require zinc as an essential trace element. To identify the detailed function of zinc in fungal pathogenicity, we carried out cDNA microarray analysis using the model system of Aspergillus fumigatus, a fungal pathogen. From microarray analysis, we found that the genes involved in gliotoxin biosynthesis were upregulated when zinc was depleted, and the microarray data were confirmed by northern blot analysis. In particular, zinc de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 60 publications
1
37
1
Order By: Relevance
“…Yet, its singularity has been virtually overlooked [see however studies such as (Bütof et al , 2019)]. Unexpectedly, it was recently observed that the Aspergillus fumigatus mycotoxin, gliotoxin, had a function specifically involving zinc (Seo et al , 2019), and, because this metabolite could act as a specific zinc chelator, this opens up approaches to investigate in depth the role of zinc.…”
Section: Figmentioning
confidence: 99%
“…Yet, its singularity has been virtually overlooked [see however studies such as (Bütof et al , 2019)]. Unexpectedly, it was recently observed that the Aspergillus fumigatus mycotoxin, gliotoxin, had a function specifically involving zinc (Seo et al , 2019), and, because this metabolite could act as a specific zinc chelator, this opens up approaches to investigate in depth the role of zinc.…”
Section: Figmentioning
confidence: 99%
“…By reducing the free zinc ion concentration inside neutrophils, a host can inhibit the growth of pathogens, and pathogens must look for other ways to survive. Our previous report showed that upregulation of gliotoxin production by zinc deprivation occurs in neutrophils [ 55 ]. In addition, upregulation of the metabolism of other metals is induced by zinc deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of this interconnection has been established in Fusarium fusjikuroi, since TOR controls—partially through AreA—the bikaverin biosynthetic genes [ 113 ]. Moreover, A. fumigatus produces more gliotoxin in Zn-limiting conditions than in Zn sufficiency and, surprisingly, Δ zafA is unable to produce gliotoxin [ 98 ]. The regulatory mechanism of gliotoxin biosynthesis by zinc has recently been described and matches what happens during infection.…”
Section: Interaction Between Metabolic Pathwaysmentioning
confidence: 99%
“…The regulatory mechanism of gliotoxin biosynthesis by zinc has recently been described and matches what happens during infection. The low concentration of Zn upregulates the zafA gene, which, in addition to upregulating Zn-metabolism genes, upregulates expression of the gliotoxin biosynthetic cluster through GliZ activation [ 98 ]. The association between a low concentration of Zn and this toxin could be a response to overcome the nutritional and innate immunity of the host, since gliotoxin protects against phagocytosis [ 114 ] and Zn depletion is a common mechanism of host defense.…”
Section: Interaction Between Metabolic Pathwaysmentioning
confidence: 99%